Cephalometric evaluation of the effect of third molar eruption on skeletal facial height - Mostafa Shahabi; Amin Mahdaviasl; Javad Faradmal; Seyedeh Maryam Tayari; Amirabbas Jafari; Mehrnoush Rostampour (Isfahan University of Medical Sciences, 2012)
AbstractIntroduction: The influence of third molar eruption on vertical facial growth has been evaluated less frequently by researchers. The aim of this study was cephalometric evaluation of the effect of third molar eruption on skeletal facial height.Materials and Methods: The subjects in this cross-sectional/analytical study consisted of thirty patients with four completely erupted third molars with proper occlusal relationships (group A) and thirty patients without third molars (group B). All the subjects were 19‒24 years of age and had Class I occlusal relationship. None of the subjects had received any orthodontic and surgical treatment. Cephalograms of subjects were traced carefully. The mean of parameters measured in both groups were compared by independent t-test (α = 0.05).Results: Means of Frankfort mandibular angle (FMA) in groups A and B were 32.26 ± 5.82 and 27.20 ± 2.53 degrees, respectively, with significant differences between the two groups (p value = 0.001). Means of gonial angles in groups A and B were 123.86 ± 1.26 and 124.5 ± 4.88 degrees, respectively, with no significant difference between the two groups (p value = 0.491). Regarding ANB and SNA angles, no significant differences were observed between the two groups (p value = 0.335) and (p value = 0.127), respectively. However, there were significant differences between the two groups in relation to SNB angle (p value = 0.05). There were significant differences in relation to posterior facial height: anterior facial height ratios and sella‒ nasion distances between the two groups (p value = 0.001). However, there were no significant differences between the two groups in relation to nasion‒ menton distances (p value = 0.733).Conclusion: Craniofacial development in patients with completely erupted third molars is different from those with no third molars. Patients with third molars have larger FMA angles and greater posterior facial height (PFH). Eruption of third molars does not influence the gonial angle.Key words: Cephalometry, Third molar, Tooth eruption.